Questions and Answers about the National Flood Insurance Program - Thomas Ruppert (EDIS)
Established by Congress in 1968 because the private market stopped offering flood insurance, the NFIP provides federally backed flood insurance to property owners in participating communities. This 11-page fact sheet covers topics such as: why buy flood insurance, recent changes, flood zones and insurance rate maps, ways to reduce premiums, rate increases for pre-1974 structures, and actions communities can take to lower citizen premiums related to climate change and sea-level rise. Written by Thomas Ruppert and published by the UF Department of Sea Grant, August 2015.